2013
DOI: 10.3810/psm.2013.11.2032
|View full text |Cite
|
Sign up to set email alerts
|

Using Viscosupplementation to Treat Knee Osteoarthritis

Abstract: This article provides physicians specializing in nonsurgical sports medicine with an overview of viscosupplementation as a treatment for osteoarthritis (OA) pain. Osteoarthritis is a painful, disabling condition that is becoming more prevalent in patients and is generally treated using conservative nonpharmacologic measures. If conservative measures are unsuccessful at alleviating pain, current recommendations include prescribing acetaminophen and nonsteroidal anti-inflammatory drugs to patients. However, long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
4
3
0
Order By: Relevance
“…The effectiveness of pain reduction was more durable in HA group compared to CS. This was like what previous studies also provide (Ray 2013 ). At the end of the third month, pain score increased after decreasing at first and second month endpoints.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The effectiveness of pain reduction was more durable in HA group compared to CS. This was like what previous studies also provide (Ray 2013 ). At the end of the third month, pain score increased after decreasing at first and second month endpoints.…”
Section: Discussionsupporting
confidence: 89%
“…Corticosteroids are other medications used as non-expensive pain modifying intra-articular injections (Bellamy et al 2006 ), but there are no definite long-term benefits (Ray 2013 ). These two categories of intra-articular injections need to be clinically evaluated comparatively to assign their indications, contra-indications, cost-benefits and hence, to find their solid location in the algorithmic approach to the treatment of OA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness was more durable with intraarticular hyaluronic acid as compared to steroid. The results were similar to a previous study by Ray et al 21 Heyworth et al did a prospective, randomized clinical study comparing hyaluronic acid, steroid, and placebo. 22 They found that the both steroid and placebo groups showed significant pain relief for ten weeks and its effect disappeared by 12 weeks, whereas, the patients in hyaluronic acid group continue to have pain relief until 26 weeks.…”
Section: Discussionsupporting
confidence: 88%
“…Intraarticular injected HA therapy shown to have prolonged effects in relieving pain compared to other similar treatments. This is consistent with other published studies to date [14,29,30].…”
Section: Discussionsupporting
confidence: 94%